Reconhecimento, redistribuição e as ambivalências do discurso sobre o Bolsa Família - Josué Pereira da Silva (Ciências Sociais Unisinos)
The article analyzes the Bolsa Família, the main Brazilian income transfer program, by approaching it through the debate recognition-redistribution. My intention is to see to what extent this controversy over recognition and redistribution helps to elucidate some aspects of the discourse on the Bolsa Família, mainly its ambivalence in characterizing what should be an emancipatory politics. For that reason, the article concentrates upon the analysis of the relationship between the conditionalities of this distributive program and the ideal of emancipation postulated by the different analysts.